2006
DOI: 10.1002/mnfr.200600003
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, fatty acid analysis and protein digestibility‐corrected amino acid score of three Mediterranean cephalopods

Abstract: Proximate composition, fatty acid analysis and protein digestibility-corrected amino acid score (PDCAAS) in three commercially important cephalopods of the Mediterranean sea (cuttlefish, octopus and squid) were determined. The results of the proximate analysis showed that these species had very high protein:fat ratios similar to lean beef. Docosahexaenoic, palmitic and eicosipentaenoic acid were the most abundant fatty acids among analyzed species. The amount of n-3 fatty acids was higher than that of saturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
40
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 18 publications
12
40
0
3
Order By: Relevance
“…This interpretation also seems to be valid for the cephalopod E. massyae, a species that exhibited a small content of lipid. The protein concentration reported by Zlatanos et al (2006) for the common octopus, Octopus vulgaris, was ca. 75% dw.…”
Section: Proteinmentioning
confidence: 98%
See 1 more Smart Citation
“…This interpretation also seems to be valid for the cephalopod E. massyae, a species that exhibited a small content of lipid. The protein concentration reported by Zlatanos et al (2006) for the common octopus, Octopus vulgaris, was ca. 75% dw.…”
Section: Proteinmentioning
confidence: 98%
“…According to Rosa et al (2005) cephalopods stockpile lipid in the digestive tract and have low concentrations of lipid in muscles (concentrations around 5% of the dry weight). Zlatanos et al (2006) and Ben-Youssef et al (2008) reported ca. 6.0% (converted to dw) of lipid in the muscles of the octopus Octopus vulgaris from the Mediterranean Sea.…”
Section: Lipidmentioning
confidence: 99%
“…These fatty acids are of great importance to humans for the prevention of coronary heart disease (Mozaffarian et al, 2005). Although cephalopods contain low levels of fat, it is rich in n−3 fatty acids (Zlatanos et al, 2006). While, seafood can be a highly nutritious component of human diet, the contaminated, imported or domestic seafood can cause foodborne illnesses, with problems ranging from mild gastrointestinal discomfort to neurological damage (GAO, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Em Foram observados altos níveis de ácido palmítico (C16:0), com valores variando decrescentemente ao longo do tempo (16,15 a 11,23%); e esteárico (C 18:0), o qual apresentou um teor expressivo no mês de julho (16,36%). Zlatanos et al (2006), avaliando a composição química de cefalópodes do Mediterrâneo, inclusive octópodes, indicaram que os ácidos graxos mais abundantes eram os ácidos docosahexaenoico, o palmítico e o eicosapentaenoico. Os níveis de C16:0, nesta pesquisa, estão abaixo daqueles revelados por Domínguez, Cortés e Várquez (2004), 16,5 a 21,6%, em juvenis de polvo e dos reportados por Sinanoglou e Miniadis-Meimaroglou (1998), 17,27 a 26,66%, em cefalópodes do Mediterrâneo.…”
Section: Methodsunclassified